ANALISIS PERAN KEPUASAN WISATAWAN MEMEDIASI PENGARUH ATRIBUT WISATA HALAL TERHADAP MINAT BERKUNJUNG ULANG PANTAI SYARIAH BANYUWANGI - Dyah Ayu Kunthi Puspitasari (Yos Soedarso Economic Journal (YEJ), 2020)
The growing consumer interest in the halal sector, especially tourism, is accompanied by the awareness of tourists in choosing tourist destinations that have implemented sharia principles. Opportunities like this should be immediately followed up by tourism managers because they relate to the marketing strategies they have to do. Travelers who have had a satisfying travel experience will voluntarily revisit these tourist destinations and will recommend them to friends, relatives, and colleagues. That way, the tourism manager must meet the needs of tourists so that they are satisfied and foster interest in revisiting these tourist destinations. This research is a quantitative research by conducting a survey using 180 samples, namely tourists on the Banyuwangi Syariah Beach. The analysis tool used is Warp-PLS 3.0. The results found are that it is known that tourist satisfaction mediates the full influence of the attributes of halal tourism on the interest in revisiting.Â Â Keywords : Islamic Attributes of Destination, Interest in Revisiting, Tourist Satisfaction, Halal Tourism.